An Analysis of Youth Deradicalization Programs in Northeast Nigeria: A Study on Boko Haram - Salihu, Mustapha (European Scientific Journal, ESJ, 2021)
Using qualitative secondary analysis, the research examine the effects of Operation Safe Corridor (OSC), a home-grown prison-based deradicalization program targeted at low-risk Boko Haram combatants, and Yellow Ribbon Initiative, an education-based recivilization program designed for young adult women associated with Boko Haram. Together with pioneer countries like Saudi Arabia and Indonesia, the structural design and implementation of OSC remain shrouded in utmost secrecy. Even though it claims to have rehabilitated over 2,000 ex-Boko Haram combatants, there is no medium to independently ascertain these claims. Relatedly, the Yellow Ribbon Initiative also claimed to have successfully reintegrated thousands of women, with little to no means to validate their claims independently. Premised on the need to implement context-specific, inclusive and robust counterinsurgency programs, the research takes issues with both programs. Furthermore, the lack of accountability and transparency in the operations of both programs put to question their credibility and objectiveness. Alternatively, the research suggests the need for a paradigm shift from deradicalization to counter-radicalization, as this will put the government on the offensive side against radicalization. If targeted at volatile communities, counter-radicalization could be designed to address underlying causalities such as unequal education opportunities and poor social infrastructure, which will in turn foster a sense of belongingness in deprived and impoverished youths in the Northeast.